2022
DOI: 10.3390/jcm11174987
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Left Atrial Longitudinal Strain in the Diagnosis of Acute Cellular Rejection in Heart Transplant Recipients

Abstract: Our aim was to investigate the role of left atrial longitudinal strain (LALS) in the non-invasive diagnosis of acute cellular rejection (ACR) episodes in heart transplant (HTx) recipients. Methods: We performed successive echocardiographic exams in 18 consecutive adult HTx recipients in their first year after HTx within 3 h of the routine surveillance endomyocardial biopsies (EMB) in a single center. LALS parameters were analyzed with two different software. We investigated LALS association with ACR presence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Although the association of absolute NT-proBNP levels with acute cellular rejection is weak, temporal changes provide important clinical information [11]. The neurohormone's temporal changes were also associated with temporal changes in the LA reservoir strain, suggesting a pathophysiological link between the two biomarkers and justifying Rodriguez-Diego's findings about reservoir strains' usefulness in detecting rejection episodes [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the association of absolute NT-proBNP levels with acute cellular rejection is weak, temporal changes provide important clinical information [11]. The neurohormone's temporal changes were also associated with temporal changes in the LA reservoir strain, suggesting a pathophysiological link between the two biomarkers and justifying Rodriguez-Diego's findings about reservoir strains' usefulness in detecting rejection episodes [6].…”
Section: Discussionmentioning
confidence: 99%
“…As a non-Doppler technique, it is also less dependent on anatomical variations and insonation angle. Similarly to LV and RV deformation parameters, LA reservoir strain may have a role in detecting acute cellular rejections after HTX [ 6 , 7 , 8 ]. Zhu et al demonstrated that LA functions by longitudinal strain are significantly different (impaired) compared with controls, irrespective of surgical technique [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…An association between increased ventricular filling pressures and reduced atrial strain has been observed ( 28 ). Furthermore, a recent study hinted at a possible role of LA-PALS in detecting ACR ( 29 ). Rodriguez-Diego et al found a significant decrease in PALS in presence of any degree of ACR, even though significant inter-vendor strain reproducibility was reported ( 29 ).…”
Section: Echocardiographic Assessment Of Diastolementioning
confidence: 99%
“…Furthermore, a recent study hinted at a possible role of LA-PALS in detecting ACR ( 29 ). Rodriguez-Diego et al found a significant decrease in PALS in presence of any degree of ACR, even though significant inter-vendor strain reproducibility was reported ( 29 ). A possible explanation for this finding might be found in the role of PALS in detecting subtle diastolic changes related to ACR episodes, in which different grades of inflammation affect the myocardium.…”
Section: Echocardiographic Assessment Of Diastolementioning
confidence: 99%